Biological control of Aspergillus flavus with Pseudozyma hubeiensis yeast from nutmeg (Myristica fragrans Houtt.) - Susilowati, Dwi N; Deswanti, Cahyani Hasna; Radiastuti, Nani; Sri Rahajoeningsih; Suryadi, Yadi; Supriadi; Nurul Hidayah; Sri Widawati; Setyowati, Ninik (Penerbit Universiti Kebangsaan Malaysia, 2025)
Yeasts are potential biocontrol agents for Aspergillus flavus, an aflatoxin-producing fungus that is present in various agricultural products, including nutmeg. This study aimed to obtain yeast isolates from nutmeg (seeds, pulps, and leaves), characterise them, and identify their antagonistic effects on A. flavus. The antagonistic activities toward A. flavus were determined by a dual-culture method. Moreover, the possible mechanism responsible for these antagonistic effects was also analysed. The results showed that 51 yeast isolates were successfully isolated from nutmeg. The inhibition percentages of 47.25 ± 1.66% (isolate DP 1341a) and 55.98 ± 1.31% (isolate DP 1342) were statistically significant (p < 0.05). The antagonistic mechanisms of the DP 1341a isolate were associated with the production of volatile organic compounds (32.79 ± 1.01%), a chitinolytic index (2.51 ± 0.55), and hyperparasitism but not toxin activity. Moreover, the DP 1342 isolate produced volatile organic compounds (54.33 ± 3.13%), exhibited toxin activity (2.74 ± 0.22) and exhibited hyperparasitism but did not exhibit chitinase activity. Molecular identification showed that the two yeast isolates (DP 1341a and DP 1342) were identified as Pseudozyma hubeiensis with sequence similarity > 99%. Therefore, the selected yeast isolates, P. hubeiensis DP 1341a and DP 1342, could be further developed as biological control agents for A. flavus. This finding will also be useful for improving biological control agents as an eco-friendly and economically viable disease management strategy.